Implementasi Pembelajaran berbasis Proyek dalam Meningkatkan Keterampilan Kolaborasi pada Mata Kuliah Pengembangan Media Pembelajaran: Implementation of Project-Based Learning in Improving Collaboration Skills in the Learning Media Development Course - Ilma, Silfia; Rafiqa, Syarifa (ITScience (Information Technology and Science), 2024)
Collaboration skills play an important role in the success of prospective teacher students. Collaboration skills provide an opportunity for prospective teacher students to develop themselves. This study aims to improve students' collaboration skills in the learning media development course. This study uses a classroom action research (CAR) approach. The data collection technique is observation. The results of the study indicate that project-based learning makes a major contribution to improving students' collaboration skills. In cycle 1, the average student collaboration skills were 67.50 in the collaborative category. While in cycle 2, the average student collaboration skills were 81.25 in the very collaborative category. Project-based learning provides a good response for students to improve collaboration skills. In addition, project-based learning is able to facilitate creative thinking.